Dental arch dimensions and palatal height in children with Turner syndrome - Bajraktarova Miševska, Cvetanka; Kočova, Mirjana; Kanurkova, Lidija; Curcieva Cuckova, Gabriela; Maneva, Marija; Bajraktarova Valjakova, Emilija (South European Journal of Orthodontics and Dentofacial Research (SEJODR), 2017)
Introduction: A complete or partial absence of an X chromosome in girls with Turner syndrome (TS) has an impact on dental archmorphology. The aim of this study was to analyze the sizes of dental arches as well as the height of the palatal vault in patients withTS, and to determine the influence of various karyotypes on the study variables.Materials and methods: The study population sample consisted of 40 TS female patients, aged 9.2 to 18 years, and 40 healthy females aged 9.3 to 18 years, as the control group. The TS patients were subdivided according to karyotype (monosomy X, mosaic, andisochromosome). Dental arch width and length, and palatal height were measured directly on plaster dental casts.Results: The results showed differences in the dental arch dimensions between TS and control groups. The maxillary dental arch was narrower and shorter, but the mandibular arch was shorter and of normal width in the TS group. The palate in TS patients were normal in height and did not differ from those of the control subjects. Although the dental arch dimensions and palatal height were slightly reduced in mosaic and isochromosome karyotypes compared with those in 45,X females, the investigation revealed nosignificant differences between the karyotypes.Conclusions: Our findings indicate that the reduction of X chromosomal genetic material in Turner syndrome females results inthe reduction of dental arch dimensions, which is further reflected in the increased frequency of malocclusion in these individuals. Importantly, this study demonstrates that palatal height is normal, contrary to some reports in the literature. It is further significantthat the TS karyotype does not affect dentoalveolar morphology and palatal height.